A Preliminary inventory of alien and cryptogenic species in Monastir Bay, Tunisia: spatial distribution, introduction trends and pathways - CHEBAANE, SAHAR; SEMPERE-VALVERDE, JUAN; DORAI, SAHBI; KACEM, ADNEN; SGHAIER, YASSINE RAMZI (Mediterranean Marine Science, 2019)
The Mediterranean Sea is a marine biodiversity hotspot under threat. One of the major impacts on its biological resources and services comes from the invasiveness of non-indigenous species (NIS). Nevertheless, NIS monitoring programs in the south basin of the Mediterranean Sea are in an early implementation stage. This study aims to describe NIS and cryptogenic species distribution in Monastir Bay (Tunisia) and to identify risk areas for the introduction and spread of invasive species, providing a baseline for future monitoring programs. To this end, a series of Rapid Assessment Surveys were carried out to identify NIS and cryptogenic species in one marina, five fishing ports, two aquaculture farms and the Special Conservation Area of the Kuriat islands. 24 species were found, of which 11 constitute new records for Monastir Bay, which represent a 33.3% of the total NIS reported in this Bay. Assemblages differed between substrata types, being NIS more abundant in artificial than in natural substrata. Regarding locations, Cap Monastir Marina was the most invaded site, the most transited by vessels and the only one visited by international sailing. Hence, this marina constitutes the main risk area to be monitored, although the fishing ports and fishing farms in the semi-enclosed coastal lagoon of Monastir Bay can also be considered as risk areas. Nevertheless, more research effort is needed in Monastir Bay in order to update the records of NIS and cryptogenic species and increase insight on the ecological evolution of these species and their related impacts on natural communities and marine resources.